The Impact of Economic Growth and Unemployment on Poverty Rates in Indonesia 2011-2024 - Melvany Agustini Sinurat; Elsa Situmorang; Novianti Naibaho; Selfiana Lumban Batu; Irma Herliza Rizki (Outline Publisher, 2026)
This study aims to analyze the effect of economic growth and unemployment rates on poverty rates in Indonesia during the period 2011 to 2024. The method used is a quantitative approach with multiple linear regression analysis, where secondary data is obtained from the publication of the Central Statistics Agency (BPS). The results of the study indicate that both economic growth and unemployment have a significant effect on poverty rates. Economic growth has a positive effect on poverty, indicating that an increase in economic growth is actually followed by an increase in the number of poor people, allegedly due to non-inclusive growth. Meanwhile, the unemployment rate shows a strong positive and significant effect on poverty. Simultaneously, both variables have a significant effect on poverty with a coefficient of determination of 68%, meaning the model can explain 68% of the variation in poverty rates. This finding confirms that economic growth needs to be accompanied by an expansion of employment opportunities in order to truly reduce poverty rates.